Malaysian SME’s Contractors Adoption of Building information Modeling (BIM) - Mohd Zul Aswad Zulkifli,; Noor Akmal Adillah Ismail,; Noorsaidi Mahat,; Mohd Dzuliqyan Jasni,; Sheikh Ali Azzran Sh Said,; Mohd Iskandar Abd Malek, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Building Information Modelling (BIM) is a modelling technology that provides construction professionals with digital tools for use in project planning, design, monitoring, and control. The potential advantages of putting BIM into practice are known to the Malaysian government. The Malaysian government has taken a number of steps to promote BIM in the hopes that Malaysian construction industry experts will utilize it extensively. However, significant difficulties are delaying the introduction of BIM in Malaysia. Implementing BIM typically presents difficulties for smaller businesses. Even though there are numerous benefits to utilizing BIM, small and medium-sized construction companies are still cautious to do so in the course of their work. This study examines BIM adoption in Malaysian small and medium-sized construction firms. The present degree of BIM adoption in Malaysia’s construction industry as well as the best tactics to encourage SME contractors in Malaysia’s construction industry to embrace BIM more effectively were the subjects of a questionnaire survey that was conducted. According to the survey’s results, SME contractors are still trailing behind in adopting BIM due to a number of obstacles that stand in the way of its adoption. In order to increase BIM adoption among SME contractors, it is crucial that government agencies successfully promote and encourage BIM use across the whole Malaysian construction sector. The importance of this study is in gathering data on the extent of BIM adoption among SME contractors, which might be utilized as a benchmark and reference for the development of BIM in the Malaysian construction industry.